Development of business entities by increasing capitalization of goodwill - Mihail Nikolaevich Dudin; Robert Mikhailovich Nizhegorodtsev; Vladimir Dmitrievich Sekerin (Вестник Пермского университета: Серия Экономика, 2016)
In the context of the economy’s transformation from its industrial to post-industrial form, the role of intellectual capital is getting more important, which is reflected in a significant difference between the market value and book value of capital of business entities. Therefore, study of such a specific economic category as goodwill is of great current interest. The article is aimed at studying directions for development of business entities by increasing capitalization of goodwill. The methodical framework of the article is based on contrastive and morphological methods of analysis. The nature and the content of economic categories "goodwill" and "capitalization" have been analyzed, the relationship between goodwill and intellectual capital of business entities have been defined. It has been found that the most significant components of goodwill are such factors as business relations, brand prestige, quality of management and management technologies, business reputation of entities. In today’s economy a significant part of a company’s market value is created due to the efficient use of intellectual capital. Financing of innovative projects and support for effective marketing policy require significant investments into intangible assets. Thus, internally generated goodwill becomes the dominant factor, basic for the company’s market value and its capitalization. Practical application of the results of this work will make it possible to foster business entities’ focusing on innovative and intellectual activity, which will help companies to achieve greater competitiveness in the post-industrial market.